Empowering township SMME's through appropriate sourcing strategies a case of Gauteng Provincial Government - Mulibana, Lavhelesani (University of Limpopo, 2016)
The post apartheid Republic of South Africa experiences several economic challenges that need urgent attention. These economic challenges include poverty, unemployment, slowing economic growth, high supply of unskilled labour, skills shortages, and an ever-escalating crime rate amongst others. In an attempt to resolve these economic challenges, the South African Government targeted the SMME sector as an economic empowerment vehicle for historically disadvantaged individuals. This follows the evident role of SMMEs in the creation of employment opportunities, poverty alleviation and contribution to GDP, amongst others. Over the years after the dawn of democracy, public procurement has been used as a tool for local economic development. The South African Government has therefore recently emphasised the empowerment of Township SMMEs through state procurement. The purpose of the research was to investigate the extent to which sourcing strategies provide a mechanism for public sector SCM to empower Township SMMEs. The qualitative methodology was used to collect and analyse the data using the case study design. The research revealed that procurement opportunities can be provided to Township SMMEs through several appropriate sourcing strategies, and other procurement methods. Nonetheless, the research further revealed that there are constraints that may hinder the successful empowerment of Township SMMEs through the application of the identified sourcing strategies and procurement methods. Such constraints have to be taken into account and addressed to ensure that the objectives behind the empowerment of Township SMMEs are realised.
Thesis (MBA.) -- University of Limpopo, 2016
Keywords: Empowerment; Township SMME's; Economic growth; New business enterprises